PENGARUH KONSENTRASI EKSTRAK DAUN KALE DALAM SEDIAAN KRIM TERHADAP KARAKTERISTIK FISIK, STABILITAS FISIK, AKTIVITAS ANTIOKSIDAN DAN HEDONIK - ulva faujiarti; liandhajani liandhajani (Pusat Penelitian dan Pengabdian Masyarakat Politeknik Harapan Bersama, 2022)
Kale leaf (Brassica oleracea var. acephala) is a type of leaf vegetable plant from thefamily Brassicaceae which has a high secondary metabolite content, one of which is rich in anthocyanin pigments which have antioxidant properties which are provided in the form of cream. The most commonly used cosmetic preparations for skin care are cream dosage forms because the cream is easy to spread evenly on the skin and is not sticky. This study aims to determine the effect of the concentration of kale leaf extract (Brassica oleracea var. acephala) on physical characteristics, physical stability, antioxidant and hedonic activity. The research stages include macerating kale leaves with 70% ethanol, then making cream with variations in concentrations of 0.5%, 1.0% and 1.5%, then physical characteristics testing includes organoleptic tests, homogeneity tests, pH tests, viscosity tests, and spreadability test. Physical stability testing using themethod cycling test, antioxidant activity testing using the DPPH method and hedonic testing using a questionnaire. Analysis of the data for physical characteristics, antioxidant activity using linear regression and descriptive hedonic and physical stability using SPSS 25. The results of the physical characteristics of kale leaf cream showed that the greater the concentration of extract in the preparation, there was an increase in pH and viscosity tests, while the spreadability test occurred. decline. The physical stability of the cream with extract concentrations of 0.5%, 1.0% and 1.5% showed a significant value because of the effect of different concentrations of kale leaf extract on pH, spreadability and viscosity. In testing the antioxidant activity of cream preparations of 70% ethanol extract of kale leaves, the greater the concentration of kale leaf extract, the greater the antioxidant activity. In hedonic, the respondents preferred the most, namely the fourth formula with an extract concentration of 1.0%.